Human development from middle childhood to middle adulthood: growing up to be middle-aged - Pulkkinen, Lea (Routledge, Taylor & Francis Group, 2017)
Preface -- Introduction to the Jyväskylä Longitudinal Study of Personality and Social Development -- How the longitudinal study began -- The execution of the longitudinal study -- Reflections on the research process -- The development of personality and psychological functioning -- Theoretical frameworks for the study of socioemotional development -- The person as social actor -- The person as motivated agent -- The person as autobiographical author and an "experiencer" of life -- Personality and psychological functioning -- The development of social functioning -- Social development and social functioning -- Problems in social functioning -- Health behavior -- The family and its care functions -- Work as a sphere of life -- Epilogue -- Navigating through the spheres of life -- The integrated model for personality and social and psychological functioning -- A credo -- References